Novel archaeological and palaeontological findings in cave and palaeoriver landscapes of inland northeast Arabia - Huw S. Groucutt; Mathew Stewart; Faisal Al-Jibreen; Mesfer Al-Qahtani; Mahmoud Al-Shanti; Eric Andrieux; James Blinkhorn; Nicole Boivin; Paul S. Breeze; Nick Drake; Abdullah Memesh; Yahya Mufarreh; et al. (PLoS ONE, 2025)
Knowledge about environmental change and the evolutionary history of hominins in Arabia has been rapidly developing over the last two decades. Interdisciplinary research on humans and environments across the vast and heterogenous landmass of the Arabian Peninsula remains, however, highly spatially uneven. Here we present the results of archaeological, hydro-geological, and palaeontological research in inland northeastern Arabia, a poorly studied area with diverse landscape features including caves, palaeorivers, and chert outcrops. Hominin use of the landscape appears to be sparse in comparison to other regions of Arabia, though archaeological evidence spanning from the Lower Palaeolithic to the historic era was identified, including finds from the Middle Palaeolithic, which is the most well represented period. The caves of inland northeast Arabia contain a rich record of past climate change in the form of speleothems, as well as abundant faunal assemblages. Our survey results highlight the significant potential of these records to cast light on environmental, faunal, and cultural changes over time while demonstrating regional variation across Arabia.